Upaya Peningkatan Kemampuan Berpikir Kreatif Mahasiswa Dengan Pembelajaraan Kooperatif Berbasis Android - Winata, Anggun; Cacik, Sri; Sulistyaningrum, Heny (Universitas Nusantara PGRI Kediri, 2020)
21st century skills include critical thinking, creative, collaborative and communicative. Early 21st century skills still show low results. The ability to think creatively is one of the important skills in 21st century abilities in addition to other abilities. The research aims to improve the ability to think creatively through Android-based cooperative learning. This study uses an experimental research type, a pre-experimental research design, and a one group pretest posttest design type. Analysis of research data in the form of creative thinking ability test sheets using indicators (1) Fluency, (2) Flexibility, and (3) Novelty (novelty). Data analysis uses the normalized gain score formula. The results of the study concluded that (1) the results of the pretest indicators of fluency, flexibility, and novelty were 2.85; 1.71; and 1.04. (2) the results of the posttest indicators of fluency, flexibility, and renewal respectively were 3.14; 3.02; and 3.35. (3) Students' creative thinking skills can be improved on the three indicators through android-based cooperative learning. Indicators of fluency and flexibility obtain moderate results with successive results of 0.50 and 0.54. The novelty indicator gives the highest result, which is 0.78.